Needs Analysis to Develop Critical Thinking Skills Assessment Integrated with ESD in Phase F Physics Learning - Resti Supendi; Emiliannur Emiliannur; Hamdi Hamdi; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
Critical thinking skills are an important competency in 21st-century physics learning. Ideally, assessments should not only measure students' conceptual understanding but also facilitate the development of critical thinking skills through contextual learning integrated with the principles of Education for Sustainable Development (ESD). However, preliminary findings indicate that students' critical thinking skills are still low, existing assessment practices are not aligned with critical thinking indicators, the characteristics of electronic assessments (e-assessments) have not been optimally implemented, and the integration of ESD in assessments is still limited. Based on these findings, this study aims to analyze the need for developing an integrated electronic assessment of ESD for critical thinking skills on the topic of Particle Motion Dynamics. A quantitative descriptive method was used involving 20 students of grade XI Phase F at SMA Muhammadiyah 3 Padang. Data were collected through critical thinking tests, questionnaires, document analysis, and interviews. The results showed low critical thinking skills (39.79%), inadequate implementation of ideal e-assessment characteristics, and low integration of ESD aspects in assessment practices. These findings indicate the need for the development of electronic assessments (e-assessments) integrated with Education for Sustainable Development (ESD), which are contextual, interactive, and capable of supporting the improvement of students' critical thinking skills in physics learning.